Experimental investigations on tension based tension leg platform (TBTLP) - Rao, D. S. Bhaskara; Selvam, R. Panneer; Srinivasan, Nagan (Journal of Naval Architecture and Marine Engineering, 2014)
Tension Leg Platforms (TLPs) are one of the reliable structures for offshore industry in deep waters because of its motion characteristics in heave, roll and pitch degrees of freedom. Heave motion is very important in offshore facilities and have to kept as minimum as possible. As the water depth increases TLPs suffers from some limitations and hence has to be modified to cater to deeper waters. One such concept proposed is Tension Based Tension Leg Platform (TBTLP). In this paper, experimental investigations carried out on a scaled model of a Tension Based Tension Leg Platform in regular waves are reported. This is the first ever experiments that was carried out on a scaled model of the new concept. To investigate the effect of Tension Base, experiments were also conducted on the TLP (without Tension Base) in two different water depths. RAOs have been compared for surge and heave dof of TLP and TBTLP. Numerical modeling of the TLP and TBTLP responses using ANSYS AQWA software are included as well for comparisons. DOI: http://dx.doi.org/10.3329/jname.v11i2.17341